The Effect of Good Corporate Governance, Corporate Social Responsibility, and Gender Diversity of the Board of Commissioners on the Financial Performance of Companies in the LQ45 Index in 2022–2024 - Veronica Patrisia Fernandes; usnia wati keristin (LP2M IAIN Palopo, 2025)
This study examines the integrated effects of good corporate governance, corporate social responsibility, and board commissioner gender diversity on financial performance of LQ45 companies during 2022-2024. The research employed quantitative methodology with purposive sampling, resulting in 135 observations from 45 companies. Data were collected from annual financial reports and sustainability reports published by Indonesia Stock Exchange and company websites. Variables measured included managerial ownership for corporate governance, Global Reporting Initiative Standards 2021 for CSR disclosure, female commissioner percentage for gender diversity, and Return on Assets for financial performance. Multiple linear regression analysis was conducted using IBM SPSS 26 with classical assumption testing. Results demonstrated that good corporate governance, corporate social responsibility, and board commissioner gender diversity exercise statistically significant positive influences on financial performance, collectively explaining 72.9 percent of financial performance variation. Each independent variable significantly affected firm performance, with board commissioner gender diversity demonstrating the strongest individual effect. Findings validate integrated governance frameworks recognizing that financial performance results from synergistic interactions among multiple governance mechanisms operating collectively rather than isolated factors.